Future of Internet of Things in Smart City - Erni Dianawati (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2019)
Internet of things has become a scientific field that continues to grow from time to time. unconsciously humans have relied heavily on the use of devices - IoT devices in their daily lives. in its development IoT has also become one of the technologies that plays a big role in the development of Smart City in the world. still many. in this paper we will discuss a number of issues that may arise in implementing IoT in Smart City and some of the solutions that have been reviewed.